IL-22 producing “T22” T-cells account for up-regulated IL-22 in atopic dermatitis (AD), despite reduced IL-17 producing Th17 T-cells - Nograles, Kristine E. (2009)
BACKGROUND: Psoriasis and atopic dermatitis (AD) are common inflammatory skin diseases. Up-regulated Th17/IL-23 pathway was demonstrated in psoriasis. Although potential involvement of Th17 T-cells in AD was suggested during acute disease, the role of these cells in chronic AD remains unclear. OBJECTIVE: To examine differences in IL-23/Th17 signal between these diseases and establish relative frequencies of T-cell subsets in AD. METHODS: Skin biopsies and peripheral blood were collected from chronic AD (n=12) and psoriasis (n=13) patients. Relative frequencies of CD4(+) and CD8(+) T-cell subsets within these two compartments were examined by intracellular cytokine staining and flow cytometry. RESULTS: In peripheral blood, no significant difference was found in percentages of different T-cell subsets between these diseases. In contrast, psoriatic skin had significantly increased frequencies of Th1 and Th17 T-cells compared with AD, while Th2 T-cells were significantly elevated in AD. Distinct IL-22 producing CD4(+) and CD8(+) T-cell populations were significantly increased in AD skin, compared to psoriasis. IL-22(+)CD8(+) T-cell frequency correlated with AD disease severity. CONCLUSION: Our data established that T-cells could independently express IL-22 even with low expression levels of IL-17. This argues for a functional specialization of T-cells such that “T17” and “T22” T-cells may drive different features of epidermal pathology in inflammatory skin diseases, including induction of AMPs for “T17” T-cells and epidermal hyperplasia for “T22” T-cells. Given the clinical correlation with disease severity, further characterization of “T22” T-cells is warranted, and may have future therapeutic implications.